Analisis Resiko Dan Tingkat Pengembalian Saham Terhadap Portofolio Optimal Saham (Studi Kasus pada 8 saham dari LQ-45) - Puspitasari, Ratih; Pramesti, Defani (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2011)
In 2007 the highest rate of return was the share of Astra International Tbk., amounting to 0,062204 and the lowest rate of return was Telekomunikasi Indonesia Tbk., amounting to 0,008778. While thw highest beta value was Astra International Tbk., amounting to 1,556123 and the lowest beta value was Aneka Tambang Tbk., amounting 0,017862. In 2008 the highest rate of return was the share of Telekomunikasi Indonesia Tbk., amounting to 0,019699 and the lowest rate of return was Perusahaan Gas Negara Tbk., amounting to 0,094074. While the highest beta value was United Tractors, amounting to 1,841033 and the lowest beta value was Telekomunikasi Indonesia Tbk., amounting to 0,806949. In 2009 the highest rate of return was the share of United Tractors, amounting to 0,114275 and the lowest rate of return was Telekomunikasi Indonesia Tbk., amounting to 0,040734. While the highest beta value was Astra International Tbk., amounting to 1599810 and the lowest beta value was Bank Danamon Indonesia Tbk., amounting to 0,239171. In 2007 there were six stocks of eight stocks that established optimal portofolio candidate. There were Aneka Tambang Tbk. with ERBâs value amounting to 1,740976 and PO at 2,95%; Perusahaan Gas Negara Tbk. with ERBâs value amounting to 0,101220 and PO at 31,23%; Medco Energi Internasional Tbk. ERBâs value amounting to 0,037370 and PO at 19,25%; Astra International Tbk. with ERBâs value amounting to 0,035366 ang PO at 27,21%; United Tractors with ERBâs value amounting to 0,033108 and PO at 15,53%; Bank Danamon Indonesia Tbk. with ERBâs value amounting to 0,027582 and PO at 3,84%. In 2008 none of the eight stocksformed optimum portfolio because in 2008 the companiesâ stocks were not be able to give good return for investors. In 2009 there were six of eight shares that established optimum potfolio candidate. There were Bank Danamon Indonesia Tbk. with ERBâs value amounting to 0,270912 and PO at 37,09%; United Tractors with ERBâs value amounting to 0,071652 and PO at 44,07%; Telekomunikasi Indonesia Tbk. with ERBâs value amounting to 0,061771 and PO at 3,57%; Aneka Tambang Tbk. with ERBâs value amounting to 0,060349 and PO at 1,64%; Bank Mandiri Tbk. with ERBâs value amounting to 0,059534 ang PO at 5,55%; Astra International tbk. with ERBâs value amounting to 0,059024 and PO at 8,08%. Thereby, investors can invest their funds in stocks which will be able form optimum portfolio.